Making the anaglyph map - Keresteš, Krešimir (Geodetski vestnik, 2000)
In this article the analysis of the accuracy of the coordinate estimation in a plane geodetic network is performed employing the Monte Carlo simulation method. Results obtained by this method are comparable with the conventional method of covariance matrix. Although the proposed method is numerically less efficient, it offers one important advantage: measurement errors may be arbitrarily distributed and mutually dependent random variables, whereas in conventional methods they are assumed to be indenpendent normally distributed random variables
Keywords: anaglifne karte; geodesy; geodezija; kartografija; stereoscopy; stereoskopija